Electrochemical oxidation of an acid dye by active chlorine generated using Ti/Sn(1-x)Ir O-x(2) electrodes - Oliveira, Flavio H.; Osugi, Marly E.; Paschoal, Fabiana M. M.; Profeti, Demetrius; Olivi, Paulo; Zanoni, Maria Valnice Boldrin [UNESP] (Springer, 2007)
The generation of active chlorine on Ti/Sn(1-x)Ir (x) O-2 anodes, with different compositions of Ir (x = 0.01, 0.05, 0.10 and 0.30 ), was investigated by controlled current density electrolysis. Using a low concentration of chloride ions (0.05 mol L-1) and a low current density (5 mA cm(-2)) it was possible to produce up to 60 mg L-1 of active chlorine on a Ti/Sn0.99Ir0.01O2 anode. The feasibility of the discoloration of a textile acid azo dye, acid red 29 dye (C.I. 16570), was also investigated with in situ electrogenerated active chlorine on Ti/Sn(1-x)Ir (x) O-2 anodes. The best conditions for 100% discoloration and maximum degradation (70% TOC reduction) were found to be: NaCl pH 4, 25 mA cm(-2) and 6 h of electrolysis. It is suggested that active chlorine generation and/or powerful oxidants such as chlorine radicals and hydroxyl radicals are responsible for promoting faster dye degradation. Rate constants calculated from color decay versus time reveal a zero order reaction at dye concentrations up to 1.0 x 10(-4) mol L-1. Effects of other electrolytes, dye concentration and applied density currents also have been investigated and are discussed.
Keywords: Ti/Sn(1-x)IrxO2 anodes; degradation of azo dye; dye oxidation; chlorine generation